Tobacco Tax Policy and Its Impact on Health Finance in Different Countries: A Systematic Review - Harvensica Gunnara; Rinaldi Daswito; Indra Martias; Ristina Rosauli Harianja (RRZ Scientific Publishing, 2024)
The consumption of detrimental products, such as cigarettes, has a significant impact on health financing. Smoking is a detrimental practice that has negative effects on health, and the medical expenses linked to smoking-related ailments are considerable. In response, many countries have established cigarette excise laws with the aim of mitigating the adverse effects of smoking on public health and health financing. The implementation of cigarette excise taxes has resulted in a notable reduction in cigarette consumption, an increase in government revenue, and the funding of health programmes. This study aimed to enhance the understanding of the role of tobacco excise laws in promoting sustainable health financing. This study involved the review of 8 papers, and it was conducted following the guidelines of PRISMA-P, 2015 for systematic reviews. A comprehensive literature search was conducted utilizing multiple databases, including PubMed, EBSCO, and ScienceDirect. The tobacco excise management policy has generally aligned with its intended objectives. However, certain aspects, such as reducing consumption, allocation amounts, tariff patterns, and burdens, have yet to be fully effective. Therefore, it is necessary to implement strategic measures to enhance adequacy, such as increasing the pattern of excise tariffs and allocations and ensuring accountability and transparency in implementation.